Improving the friction stir welding tool life for joining the metal matrix composites - Emamian, S.S. (Springer, 2020)
Welding matrix composites that have been formed with conventional methods produce many discontinuities which harm the quality of joints. Friction stir welding (FSW) offers an alternative method to prevent these issues. However, the existence of reinforcing particles, such as silicon carbide in metal matrix composites (MMCs), has significantly increased the wear rate of FSW tools and hence, reducing their tool life. Therefore, this research has focused on the improvement of FSW tool life in joining the aluminum matrix composites, through surface enhancement. H13 tool steel and tungsten carbide, as a base material, were used for the FSW tool, and graphene, carbon nanotubes, and diamond-like carbon were chosen for coating the FSW tool. Subsequently, the wear on the FSW tool was measured before and after welding to evaluate tool life. The result of wear measurement indicates that the wear resistance of the diamond-like carbon (DLC)âcoated tungsten carbide was higher than the others. The tool life of the coated tungsten carbide (WC)-DLC was prolonged to approximately 41. In addition, it is predicted that the FSW tool can be effective for up to 1200Â mm of weld joint. Â© 2020, Springer-Verlag London Ltd., part of Springer Nature.